Post-mortem computed tomography findings of the frozen brain. (September 2017) - Kawasumi, Yusuke; Usui, Akihito; Ikeda, Tomoya; Ishibashi, Tadashi; Funayama, Masato
Abstract: Post-mortem computed tomography (CT) is a valuable tool in forensic medicine. Determination of cause of death may require examination of a corpse found in a frozen state. However, most radiologists are unfamiliar with the post-mortem appearance of frozen organs on CT. Here we present two cases that included CT study of the frozen brain. Both bodies were naturally frozen, and autopsies showed that the cause of death was hypothermia in both instances. On post-mortem CT images, the frozen brains exhibited hypodense areas resembling infarctions, but these were not in regions dominated by blood vessels. Residual open sulci were evident, suggesting that oedema was absent. These two features are helpful when diagnosing a frozen brain on CT images. Highlights: The frozen brain shows hypodense areas resembling brain infarction on PMCT. The first feature is the presence of obvious sulci. The second feature is the lack of association with blood-vessel-dominant regions. The two additional features can aid in the recognition of the frozen brain.